Solve 2*z = w + 38 - 34, -z + 7 = 2*w for z.

3

Solve -28*j = -26*j + 4*g - 8, 5*g = j + 24 for j.

-4

Solve 5*m = -4*s - 0*s - 40, 0 = 2*s + 5*m + 30 for s.

-5

Solve u = 2*b + b - 18, 0 = -u - 3*b + 12 for u.

-3

Solve -3*u - 16 = -4*i, 5*i + 16 = -5*u + 1 for u.

-4

Solve -2*f + 3*p + 3 = f, f + 29 = -5*p for f.

-4

Solve -2*i - 14 = n - 6, -3*n - 4*i - 20 = 0 for n.

-4

Solve -4*h + 2*g = -2*h - 10, 5*h + 5*g + 15 = 0 for h.

1

Solve m + 5 = -0*m + r, 0 = 5*m - 3*r + 19 for m.

-2

Solve 3*n + 9 = l + 4, 4*n + 2*l = 0 for n.

-1